GEOMORPHOLOGICAL AND BATHYMETRIC RESEARCH ON LAKES ZERELIA OF ALMYROS (CENTRAL GREECE) - Gaitanopoulos, A.; Albanakis, K.; Vouvalidis, K. (Bulletin of the Geological Society of Greece, 2016)
The area of interest is located close to Almyros city, at the prefecture of Magnesia (Central Greece), where the twin lakes Zerelia are situated. The origin of these twin lakes is not clear, however, many hypotheses have been proposed over the years. A lack of large-scale mapping in the surrounding area and a high resolution spatial depiction of the topography, hinders the extractionof conclusions on the twin lakes’ origin. Also, previous studies have focused on surficial evidence to support hypotheses, rather than investigating the geometric characteristics and the spatial lay-out of the twin lakes. Filling this gap, measurements of depth via sonar in Zerelia lakes were performed. The bathymetric data along with the digitized, high-resolution topographic data of the surrounding terrain were imported in a Geographic Information System (GIS) environment. The area was depicted with high accuracy through DEMs and conclusions for the landscape were extracted. The above analysis contributed towards an appreciation of the intense interplay between erosional andtectonic processes in the area and deemed drainage antecedence an important element that needs to be accounted for, in any interpretation of the origin of the twin lakes Zerelia.